Incidence of Orchiectomy in Patients with Testicular Torsion Treated in the Urology Department in Hilla Teaching Hospital (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Acute torsion of the testicle(s) is one of the common emergencies in the field of urology; it results in either decrease or complete disruption of testicular blood flow, it affects about 4.5/100000 less than 25 years male. The golden period of testicular saving intervention is the first 6 – 8 hours from the onset of symptoms. The aim of this study is to obtain a statistic about patients with testicular torsion treated at our center,  concentrating on patients ended with orchiectomy. A total number of 25 patients presented to our center during the study period (2 years). After taking a full history and scrotal examination, all patients sent to Doppler scrotal ultrasonography to confirm the diagnosis and assess vascularity, and then all patients un- derwent scrotal exploration through a scrotal incision. Orchiopexy or orchiectomy was done depending on viability of the testis. Contralateral orchiopexy was done in all patients. Forty percent of our patients ended with orchiectomy, the incidence of orchiectomy was higher in patients lived in rural areas (70 %), there also was strong relationship between cold weather and the incidence of orchiectomy. The most important factor in detecting testis salvageability was the duration of symptoms before the presentation.